Policies and practices for entrepreneurial education in Malaysia :a review - Siti Farhah Fazira Shamsudin; Abdullah Al- Mamun; Noorshella Che Nawi; Azwin Md Nasir; Mohd Nazri Zakaria (Faculty of Entrepreneurship and Business,UMK, 2015)
Entrepreneurship is regarded as one of the key economic development strategies to advance a country’s economic growth and to sustain its competitiveness in facing the increasing trends of globalization. The Malaysian government has made tremendous efforts in promoting entrepreneurship education across the country. This paper therefore aims to review the programs and policies, together with empirical studies on entrepreneurial education, and its effects on students’ entrepreneurial intentions. Finally, the review of the policies and practices in Malaysia shows that the government is mostly focused on the following aspects: improving the current policy on entrepreneurship education, providing various entrepreneurship programs to increase the number of young entrepreneurs, and highlighting the need to empower entrepreneurship education among graduates of HEIs.